Distribution Transformer Load Imbalance Analysis at Universitas Bangka Belitung - Deni Irwansyah; Welly Yandi; Asmar; Wahri Sunanda; Azriyenni Azhari Zakri (Jurnal Inovasi Teknologi, 2022)
Loading between phases must always be considered in order to reduce the imbalance, which results in an increase in neutral current and loss of conductor power. Non-linear loads can cause harmonics that affect the increase in copper losses in the transformer. Harmonics can cause distortion of the voltage and current waveforms, so attention must be paid to the specified limits so as not to interfere with the performance of electrical equipment. In addition, these parameters can affect the main electrical parameters, so they must be considered at the specified limits. This study aims to analyze the condition of load imbalance, harmonic content, and the effect on power loss in distribution transformers at Universitas Bangka Belitung. Parameters were measured using a Meterel Power Meter Analyzer type MI 2592 Power Q4 for ten days with the comparative method as a data analysis method. The average current unbalanced percentage is 9.91%, with the highest value at 24.31%. Energy due to power loss in the neutral conductor is 0.46 kWh/10 days, and the total conductor loss is 18.122 kWh/10 days.